Apparent-time variation in the use of multiple cues for perception of anticipatory nasal coarticulation in California English - Georgia Zellou; Michelle Cohn (Glossa, 2024)
This study examines apparent-time variation in the use of multiple acoustic cues present on coarticulatorily nasalized vowels in California English. Eighty-nine listeners ranging in age from 18-58 (grouped into 3 apparent-time categories based on year of birth) performed lexical identifications on syllables excised from words with oral and nasal codas from six speakers who produced either minimal (n=3) or extensive (n=3) anticipatory nasal coarticulation (realized by greater vowel nasalization, F1 bandwidth, and diphthongization on vowels in CVN contexts). Results showed no differences across listeners’ identification for Extensively coarticulated vowels, as well as oral vowels by both types of speakers (all at-ceiling). Yet, performance for the Minimal Coarticulators’ nasalized vowels was lowest for the older listener group and increased over apparent-time. Perceptual cue-weighting analyses revealed that older listeners rely more on F1 bandwidth, while younger listeners rely more on acoustic nasality, as coarticulatory cues providing information about lexical identity. Thus, there is evidence for variation in apparent- time in the use of the different coarticulatory cues present on vowels. Younger listeners’ cue weighting allows them flexibility to identify lexical items given a range of coarticulatory variation across (here, younger) speakers, while older listeners’ cue weighting leads to reduced performance for talkers producing innovative phonetic forms. This study contributes to our understanding of the relationship between multidimensional acoustic features resulting from coarticulation and the perceptual re-weighting of cues that can lead to sound change over time.